'You wonder ever if you're a bad man?': Toxic masculinity, paratexts and think pieces circulating around season one of HBO's True Detective. (March 2020) - Albrecht, Michael Mario
When it premiered in 2014, the first season of HBO's True Detective received rave critical reviews. Featuring two A-list Hollywood actors, and a writer/director team who were rising stars in the industry, the show had all of the key ingredients to earn the label 'prestige TV'. However, alongside the critical claim were concomitant critiques of the show for its apparent misogyny. The season features depictions of violent crimes against women and girls and is told almost entirely from the perspective of two middle-aged men. The salient question was whether the show was misogynist or whether it was a show about misogyny. Many of these debates transpired in think pieces of online magazines and blogs such as Salon, Vulture, Jezebel, The New Yorker and The A.V. Club . In this article, I examine the ways in which these discourses of misogyny and masculinity circulate in these paratexts. Ultimately, I suggest that the question of whether the show is misogynist is less important than the fact that nuanced discussions about gender and power found a platform and an audience with a broad circulation.